Confirmation of a New Metal-poor Globular Cluster in the Galactic Bulge - Minniti, Dante (2018)
We use deep near-IR photometry of the VISTA Variables in the Vía Láctea (VVV) Survey and deep DECam PlaneSurvey (DECaPS) optical photometry to confirm the physical reality of the candidate globular cluster (GC) Minni22, which is located in the Galactic bulge. This object, which was detected as a high density region in our maps ofbulge red giants, is now confirmed as a real GC based on the optical and near-IR color?magnitude diagrams. Wealso recover three known fundamental mode (ab type) RR Lyrae stars within 2 arcmin of the cluster center. Thepresence of RR Lyrae stars also seems to confirm Minni 22 as a bonafide old and metal-poor GC. We estimate acluster reddening E(J-Ks) = 0.6 mag and determine its heliocentric distance D = 7.4 ± 0.3 kpc. The opticaland near-IR color?magnitude diagrams reveal well-defined red giant branches in all cases, including a red giantbranch bump at Ks = 13.30 ± 0.05 mag. The comparison with theoretical isochrones yields a mean metallicity of[Fe/H] = −1.3 ± 0.3 dex, and age of t ∼ 11.2 Gyr. This is a good example of a new low-luminosity(M_V = −6.2 mag) GC found in the central bulge of the Milky Way. After discussing the different ways to confirmthe existence of bulge GC candidates, we find that one of the best methods is to use the CMDs from thecombination of the DECaPS + VVV photometries